Dil bilimi temelli pedagojik çerçevede okul sözlüğü maddeleri - Devecioğlu, Miray (My University, 2023)
Sözlükler, kelimeler hakkında anlam ve kullanım bilgisi sağlayan başvuru kaynaklarıdır. Sözlük derleme, sözlükçülük ilke ve kuramlarını tartışan sözlük bilim (leksikografi), uygulamalı ve teorik olmak üzere iki alana sahip çalışma alanıdır. Sözlüklerde madde başı kelime ve onun tanımı ile ek açıklamalar içeren birime sözlük maddesi denir. Bir sözlük maddesinin madde başı kelimenin sesletim özellikleri, kelime türü ve örnek cümleler gibi hangi yapıları içereceği yani parçacıl yapının tasarımı ise sözlüğün hedef kullanıcı kitlesine göre değişiklik göstermektedir. Araştırma konusu olan okul sözlükleri hedef kullanıcı kitlesi ilk ve ortaokul öğrencileri olan bu sebeple diğer sözlüklerden farklı olarak sözlük maddelerinde pedagojik yapıları da barındıran sözlüklerdir. Bu araştırmanın problem cümlesi “Okul sözlüklerinde bir sözlük maddesinde bulunan pedagojik ve dil bilimsel yapılar nelerdir?” olarak belirlenmiştir. Araştırma ile dünyadaki okul sözlüklerinde var olan farklı yapıların bir listesinin oluşturularak Türkçe okul sözlükleri için bir şablon geliştirilmesi amaçlanmıştır. Araştırmanın modeli nitel, izlenen yöntem betimleyicidir. Araştırma nesnesi olarak TDK Okullar için Türkçe Sözlük, Cambridge School Dictionary ve Dictionnaire Le Robert Scloaire seçilmiştir. Basit seçkisiz yöntem ile seçilen 191 sözlük maddesi içerik analizi ile incelenerek okul sözlüklerinde bir maddede yer alan yapıların listesi oluşturulmuştur. Araştırma sonucunda okul sözlüklerinde toplam 16 pedagojik 29 dil bilimsel olmak üzere 45 farklı yapı bulunduğu sonucuna ulaşılmıştır. Türkçe okul sözlükleri için önerilen tanım şablonunda Türkçenin sentagmatik özellikleri göz önünde bulundurularak bir kelimenin dil bilgisel işlevi cümlede aldığı yere göre değiştiği için örnek cümlelerin önemi özellikle vurgulanmıştır.

Dictionaries are reference sources that provide meaning and usage information about words. Lexicography, which discusses dictionary compilation, lexicography principles and theories, is a field of study with two areas, applied and theoretical. In dictionaries, the unit containing the per-item word and its definition and additional explanations is called an entry. The structure of a dictionary item, such as the pronounciation characteristics of the headword, word type and example sentences, in other words the design of the fragmentary structure, varies according to the target user group of the dictionary. School dictionaries, which are the subject of research, are dictionaries whose target user group is primary and secondary school students, therefore, unlike other dictionaries, they also contain pedagogical structures in their entries. The problem sentence of this research is “What are the pedagogical and linguistic structures found in a dictionary item in school dictionaries?” has been determined. With the research, it is aimed to develop a template for Turkish school dictionaries by creating a list of different structures that exist in school dictionaries around the world. The model of the research is qualitative, the method followed is descriptive. TDK Turkish Dictionary for Schools, Cambridge School Dictionary and Dictionnaire Le Robert Scloaire were chosen as research objects. A list of structures in an article in school dictionaries was created by examining 191 dictionary items selected by simple random method with content analysis. As a result of the research, it was concluded that there are 45 different structures in school dictionaries, 16 of which are pedagogical and 29 are linguistic. In the definition schema proposed for Turkish school dictionaries, the importance of example sentences is especially emphasized, since the grammatical function of a word changes according to the place it takes in the sentence, taking into account the syntagmatic features of Turkish.
School dictionary entries in a linguistics based pedagogical framework
Keywords: Definition; Dictionaries; Dil bilimi; Entry; Headword; Leksikografi; Lexicography; Madde başı; Pedagogy; Pedagoji; Sözlük maddesi; Sözlükler; Tanım Linguistics; Turkish language; Türk dili